Case report: Intrapericardial thrombus aspiration in early stage of pericardial thrombosis for cardiac tamponade complicating percutaneous left atrial appendage closure - Mo, Bin-Feng; Wu, Cheng-Qiang; Wang, Qun-Shan; Li, Yi-Gang (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Pericardial thrombosis that complicates pericardial bleeding is a life-threatening emergency in interventional cardiology, and surgery remains the only definitive treatment option. We report the first case of successful intrapericardial thrombus aspiration using a dedicated thrombus aspiration catheter in early stage of pericardial thrombosis. Case Report: A 76-year-old woman with non-valve atrial fibrillation underwent percutaneous left atrial appendage (LAA) closure for secondary prevention of stroke. A 24-mm Watchman device was deployed under fluoroscopic guidance. Post-deployment angiography revealed LAA perforation, which led to rapid onset of cardiac tamponade. Emergency pericardiocentesis was performed and the deep-seated device was redeployed at a more proximal position to seal the distal perforation. Pericardial bleeding was controlled after drainage of 400 mL of blood. However, the patient re-developed cardiac tamponade following a period of stability. The patient was diagnosed with early-stage pericardial thrombosis based on echocardiographic findings of a hypoechoic effusion in the pericardial space. Thrombus aspiration using a pigtail catheter and long sheath failed; however, we performed successful intrapericardial thrombus aspiration using a dedicated thrombus aspiration catheter. We drained 120 mL of sludge-like blood, and the patient underwent successful conservative management without surgical intervention. Conclusion: This case report highlights the potential usefulness of a percutaneous intrapericardial thrombus aspiration technique using a dedicated thrombus aspiration catheter in selected patients with early-stage pericardial thrombosis, as a less invasive alternative to cardiac surgery.